Secondary units and urban infill: A literature review - Jake Wegmann; Alison Nemirow (University of California, Institute of Urban and Regional Development (IURD), 2011)
This literature review examines the research on both infill development in general, and secondary units in particular, with an eye towards understanding the similarities and differences between infill as it is more traditionally understood - i.e., the development or redevelopment of entire parcels of land in an already urbanized area - and the incremental type of infill that secondary unit development constitutes. The paper is intended to provide background to an ongoing study of secondary unit development potential in the East Bay.
Keywords: 330